El apego para el desarrollo de las emociones básicas en los niños de inicial subnivel 2 de la Unidad Educativa Cap. Edmundo Chiriboga, en la ciudad de Riobamba, periodo 2020 2021 - Patajalo Ríos, Byron Francisco (2021)
This research was conducted at the "Cap. Edmundo Chiriboga G" Educational Unit, province of Chimborazo, as the problem indicates the scarce use of the practice of dance as a strategy in psychomotor skills, has been creating shortcomings in children to solve daily activities, therefore I have seen the need to investigate the issue raised. If we reflect on the current situation, dance has focused on the artistic style but has not been focused as a strategy to improve the gross motor skills of children from 4 to 5 years of age, this stage is one of the most important for children since they have an innate energy that must be used to the maximum. For this reason, in order to work on the basis of motor skills, a proposal was developed under the name "We learn by dancing" so that teachers of the well-known Educational Institution can implement it in class hours, developing control of the children's body movements, developing a free body expression and a complete knowledge and control of the upper and lower limbs of their body.